AKT1 and BRAF mutations in pediatric aggressive fibromatosis. (8th April 2016) - Meazza, Cristina; Belfiore, Antonino; Busico, Adele; Settanni, Giulio; Paielli, Nicholas; Cesana, Luca; Ferrari, Andrea; Chiaravalli, Stefano; Massimino, Maura; Gronchi, Alessandro; Colombo, Chiara; Pilotti, Silvana; et al.
Abstract: Aside from the CTNNB1 and adenomatous polyposis coli (APC) mutations, the genetic profile of pediatric aggressive fibromatosis (AF) has remained poorly characterized. The aim of this study was to shed more light on the mutational spectrum of pediatric AF, comparing it with its adult counterpart, with a view to identifying biomarkers for use as prognostic factors or new potential therapeutic targets. CTNNB1, APC, AKT1, BRAF TP53, and RET Sanger sequencing and next‐generation sequencing (NGS) with the 50‐gene Ion AmpliSeq Cancer Hotspot Panel v2 were performed on formalin‐fixed samples from 28 pediatric and 33 adult AFs. The prognostic value of CTNNB1, AKT1, and BRAF mutations in pediatric AF patients was investigated. Recurrence‐free survival (RFS) curves were estimated with the Kaplan–Meier method and statistical comparisons were drawn using the log‐rank test. In addition to the CTNNB1 mutation (64%), pediatric AF showed AKT1 (31%), BRAF (19%), and TP53 (9%) mutations, whereas only the CTNNB1 mutation was found in adult AF. The polymorphism Q472H VEGFR was identified in both pediatric (56%) and adult (40%) AF. Our results indicate that the mutational spectrum of pediatric AF is more complex than that of adult AF, with multiple gene mutations involving not only CTNNB1 but also AKT1 and BRAF . This intriguing finding may have clinical implications and warrants further investigations. Abstract : The aim of this study was to shed more light on the mutational spectrum of 28 pediatric aggressive fibromatosis (AF), comparing it with its adult counterpart. In addition to CTNNB1 mutation (64%), pediatric AF showed AKT1 (31%), BRAF (19%), and TP53 (9%) mutations, whereas only the CTNNB1 mutation was found in 33 adult AF. This intriguing finding, suggesting a mutational spectrum of pediatric AF more complex than that of adult, may have clinical implications and warrants further investigations.